Odpowiedź:
a)7ˣ⁺¹-7ˣ⁻¹=48
[tex]7^{x}*7-7^{x}*7^{-1}=48[/tex]
[tex]7^{x}*7-7^{x}*\frac{1}{7} =48[/tex] mnożymy *7
7ˣ*49-7ˣ=336
48*7ˣ=338 /:48
7ˣ=7¹
x=1
b)9ˣ+4*3ˣ+4=0
(3²)ˣ+4*3ˣ+4=0
3²ˣ+4*3ˣ+4=0
(3ˣ+2)²=0
3ˣ+2=0
3ˣ=-2
c)15*3ˣ⁻¹+3ˣ⁺¹+3ˣ=27
[tex]15*3^{x}*\frac{1}{3} +3^{x}*3+3^{x}=27[/tex]
5*3ˣ+3*3ˣ+3ˣ=27
9*3ˣ=27 /:9
3ˣ=3¹
x=1
d)2*3ˣ⁺¹-4*3ˣ⁻²=450
[tex]2*3^{x}*3-4*3^{x}*(\frac{1}{3} )^2=450[/tex]
[tex]6*3^{x}-\frac{4}{9} *3^{x}=450[/tex] mnożymy *9
6*9*3ˣ-4*3ˣ=450*9
54*3ˣ-4*3ˣ=4050
50*3ˣ=4050 /:50
3ˣ=81
3ˣ=3⁴
x=4
Szczegółowe wyjaśnienie: